FACTORS THAT INFLUENCE SUKUK RATINGS IN COMPANIES ISSUING SUKUK AT INDONESIA STOCK EXCHANGE - Nurmalita, Nurmalita; Mubarak, Zaki; Alfinuri, Novita Alfinuri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the effect of profitability, solvency, liquidity, leverage, and activity variables on sukuk ratings in Indonesia. The method used is logistic regression with sample data totaling 50 sukuk samples published on the Indonesia Stock Exchange in 2017-2021.This research contributes to understanding factors that affect sukuk ratings in Indonesia. The implication of this research is the importance of companies improving their financial performance in order to obtain better and higher sukuk ratings.